Dinosaurs : [4 favorite stories!]. - Maccarone, Grace; Bridwell, Norman; Schlein, Miriam; Schwartz, Carol; Donnelly, Liza.; Maccarone, Grace; Courtney, Richard, 1955-; Scholastic Inc. (New York : Scholastic, 2007)
Presents four popular dinosaur stories bound in a single volume.
Magic Matt and the dinosaur / by Grace Maccarone ; illustrated by Norman Bridwell, ill. -- What the dinosaurs saw : animals living then and now / by Miriam Schlein ; illustrated by Carol Schwartz -- Dinosaur garden / by Liza Donnelly -- Dinosaurs / by Grace Maccarone ; illustrated by Richard Courtney.
"Cartwheel books."
Cover subtitle.
1-2
Keywords: Dinosaurs -- Juvenile literature; Paleontology -- Juvenile literature